PENYEBAB TERJADINYA PENGIRIMAN BARANG MISROUTE - Muhammad Iqbal Firdaus; Suci Pertiwi (Institut Transportasi dan Logistik Trisakti, 2016)
In carrying out the delivery process PT.Trimuda Nuansa Citra transportation services company engaged in the freight forwarder. seek error does not occur for the achievement of good delivery. The purpose of this study was to determine the factors that lead to the delivery of goods misroute. Data analysis technique used is the analysis of the factors to look for a dominant factor causing misroute delivery. The results of the research that is the dominant factor causing the delivery of goods is a factor misroute machinery, equipment and infrastructure, labor factor, external environmental factors. While subfactors that most influence is the lack of motivation of labor subfactors, subfactors workplace conditions were inadequate, subfactors absence of financial incentives for couriers when performing work beyond its capacity, subfactors work procedures that are less obvious and subfactors of customer data that is not clear.